(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
Artificial Intelligence (AI) has rapidly pervaded the legal industry over the past decade. Machine learning algorithms, natural language processing, computer vision, and other AI technologies now assist with legal research, contract review, case outcome prediction, and more. While promising increased efficiency and cost savings, AI’s legal applications raise privacy, bias, and accountability concerns. This research paper overviews AI and how it’s employed in the legal field. It examines the benefits and challenges of using AI for legal purposes, discussing the ethical and legal implications around adopting such technologies in the justice system. Moreover, the paper explores how AI could transform the legal profession itself, redefining lawyers’ roles going forward. Concluding recommendations advise policymakers, legal practitioners, and researchers on responsibly harnessing AI’s potential while mitigating risks. Given AI’s capacity to improve access to justice, reduce expenses, and elevate legal service quality, its legal system utilization is paramount. However, the legal and ethical issues surrounding AI’s legal applications require addressing. The Indian government takes steps towards developing relevant regulations, indicative of increasing legislative efforts to govern AI usage in the justice arena. Across sectors like healthcare, business, and manufacturing, AI solves manifold real-world problems, driving its widespread adoption. While many law firms still rely on conventional technology and software, advanced AI integration grows in popularity as a means to boost efficiency and effectiveness. By automating routine tasks, AI frees lawyers to focus on higher-level strategic work. AI’s remarkable ascent, familiarizing the masses with chatbots and virtual assistants resulting in AI integration in the legal field presents opportunities and challenges. Although promising process streamlining, enhanced access to justice, and cost reductions, it sparks critical privacy, bias, and accountability apprehensions. This research contributes insights into AI’s legal role and recommendations for ethically responsible adoption amidst regulatory developments governing justice AI usage. The current generation witnesses’ artificial intelligence’s remarkable strides, India achieves significant milestones integrating AI across industries. In Chennai and Hyderabad, robot-themed restaurants employ robots to serve and interact with customers in English and Tamil. Law enforcement agencies leverage robotic capabilities, with a police robot deployment. Ahmadabad witnessed a pioneering tele robotic coronary intervention in 2018, where a cardiologist performed the procedure on a patient 32 km away using robotic technology. This paper also delves into AI’s legal personhood, privacy implications, advantages, drawbacks, and intersection with the law.